In vivo 3D Reconstruction of the Human Pallidothalamic and Nigrothalamic Pathways With Super-Resolution 7T MR Track Density Imaging and Fiber Tractography - Dae-Hyuk Kwon; Sun Ha Paek; Young-Bo Kim; Haigun Lee; Zang-Hee Cho (Frontiers Media S.A., 2021)
The output network of the basal ganglia plays an important role in motor, associative, and limbic processing and is generally characterized by the pallidothalamic and nigrothalamic pathways. However, these connections in the human brain remain difficult to elucidate because of the resolution limit of current neuroimaging techniques. The present study aimed to investigate the mesoscopic nature of these connections between the thalamus, substantia nigra pars reticulata, and globus pallidus internal segment using 7 Tesla (7T) magnetic resonance imaging (MRI). In this study, track-density imaging (TDI) of the whole human brain was employed to overcome the limitations of observing the pallidothalamic and nigrothalamic tracts. Owing to the super-resolution of the TD images, the substructures of the SN, as well as the associated tracts, were identified. This study demonstrates that 7T MRI and MR tractography can be used to visualize anatomical details, as well as 3D reconstruction, of the output projections of the basal ganglia.